THE EFFECT OF E-WOM ON PURCHASE INTENTION WITH CUSTOMER SATISFACTION AS A MEDIATION VARIABLE ON IPHONE SMARTPHONES (Study On Customers In Jakarta) - Viola Cahyaningrum; Sri Hartini (SEAN Institute, 2023)
This study aims (1) to analyze the effect of E-WOM on purchase intention; (2) analyze the effect of E-WOM on customer satisfaction; (3) the effect of customer satisfaction on purchase intention; (4) analyze the effect of E-WOM on purchase intention mediated by customer satisfaction. The population is all iPhone customers who have never purchased an iPhone smartphone. The total sample of 100 respondents was taken using a purposive sampling technique. Data collection techniques using a questionnaire. Data analysis using path analysis and Sobel test. The results of the study show that (1) E-WOM has a significant effect on purchase intention. (2) E-WOM has a significant effect on customer statistics. (3) customer satisfaction has a significant effect on purchase intention. (4) E-WOM has a significant effect on purchase intention which is mediated by customer satisfaction.